THE IMPACT OF LEADERSHIP STYLES ON TEACHER MOTIVATION AND ORGANIZATIONAL CLIMATE IN EDUCATIONAL INSTITUTIONS (International Journal of Food and Nutritional Sciences, 2022)
This article explores the relationship between leadership styles of school principals and theirimpact on teacher motivation and organizational climate in educational institutions. Througha comprehensive review of existing literature, three main objectives were established: toanalyze the influence of leadership styles on teacher morale, to assess the connection betweenleadership practices and school effectiveness, and to evaluate the role of demographic factorsin shaping leadership approaches. Findings indicate that transformational and participativeleadership significantly enhance teacher satisfaction and engagement, while authoritarianstyles detract from school climate. Recommendations include the adoption of professionaldevelopment programs for principals and the importance of recognizing teacherdemographics. This study highlights the critical need for effective leadership to foster apositive educational environment.